Effects of environmental changes on sandy beach biodiversity: what we can learn with small-scale patterns and processes? - Laurino, Ivan Rodrigo Abrão (2022)
Sandy beaches are coastal ecosystems largely appreciated by human society. The distribution and structure of beach biodiversity and its interaction with the physical environment are essential components for the beach\'s functioning and the provision of ecosystem services. However, sandy beaches are also vulnerable to multiple threats such as climate changes and urban development, pressures that jeopardize their biodiversity. In the present contribution, we test the effects of multiple environmental changes on beach biodiversity\'s behavior, distribution, structure, and ecological relationships. With this goal, we carried out a series of small-scale field experiments on the beaches of the northern coast of São Paulo, Brazil. We explored the effects of flooding, salinity reduction, coastal armoring (i.e., backshore seawalls), and the increase of storm-stranded debris (i.e., wrack) on the beach ecosystem. We tested the responses of benthic macrofauna to these pressures by evaluating the behavior of species, the taxonomic and functional richness of communities, their abundance and biomass, as well as their function as prey for birds. We found that simulated flooding induces the downward vertical displacement of polychaetes (i.e., Scolelepis) and isopods (i.e., Excirolana armata), changing the macrofauna distribution in the sediment column. We also noted a weaker downward displacement with freshwater than with saltwater floods for E. armata, suggesting a salinity influence on the behavior of this isopod. Salinity reductions also decreased the community richness and the probability of polychaetes forming high-abundance patches (mainly Scolelepis patches) close to freshwater streams on the beach. Coastal armoring, in turn, reduced the abundance and biomass of beach macrofaunal assemblages and influenced their composition and functional structure. Particularly, the abundance of subtidal polychaetes and molluscans, the abundance and biomass of the coleopteran Phaleria testacea, and the occurrence of predators and large body size species (> 80mm) were the patterns most impacted by coastal armoring. The coleopteran P. testacea is also the main species affected by the storm-stranded debris, presenting aggregations under wrack. However, there was no evidence that such aggregation could work as a prey hotspot for birds in the short term, considering the study area. Additionally, these aggregations under wrack were a phenomenon strongly associated with natural debris (i.e., algae and leaves), not occurring in plastic debris. We conclude that the macrobenthic biodiversity of the sandy beaches studied is sensitive to environmental changes, especially flooding events, salinity reductions, urban development, and changes in the storm-stranded wrack. The biodiversity changes evidenced here can induce, in the long-term, important ecosystem impacts on the functioning of beaches, which should be further assessed. Finally, we argue that the use of small-scale approaches can be important tools for conservation, generating early proxies (i.e., sublethal biological indicators, such as vertical displacement), useful to improve the assessment of future scenarios and monitoring programs.